The compulsory public pension and the demand for life insurance: the case of Sweden, 1884–19141. (13th June 2014) - Andersson, Lars‐Fredrik; Eriksson, Liselotte
<x xml:space="preserve">Abstract</x> We employ cost‐of‐living surveys, business archives, and firm data to examine the impact of the compulsory pension on the demand for life insurance in Sweden from 1884 to 1914—a period that covers the implementation of the first public compulsory old‐age pension reform and the take‐off of industry life insurance. As predicted on the basis of the contemporary literature on crowding‐out effects, we find that the compulsory pension reduced the demand for life insurance. Our panel‐data analysis of lapse rates on insurance policies shows a significant crowding‐out effect of pension payments. We conclude that the introduction of the general compulsory pension had a crowding‐out effect on households' holdings of insurance policies.